Assessment of the operation safety margin of the HL-LHC superconducting recombination Dipole D2 in case of helium filling failure. Issue 1 (1st May 2022) - Rousset, B; Bancel, F; Besson, N; Bon-Mardion, M; Claudet, S; Goy, T; Millet, F; Nivelon, P; Perin, A
Abstract: After the successful completion of the cryogenic performance tests of the He II heat exchanger prototype for the D2 recombination dipole of the future HL-LHC project at CERN, specific measurements were performed to determine the operation safety margin in case of abnormal operating conditions. This is particularly relevant in case of the failure of liquid helium supply in the He II cold source. For nominal operation, the liquid level is regulated at a constant value and it is not necessary to know its value very accurately. However, in case of a partial drying of the heat exchanger due to discontinuation of the helium liquid supply, it is essential to monitor the absolute value of the liquid level to anticipate any cooling malfunction. This paper describes the procedure for an accurate in-situ He II level measurement as well as for the heat loss and mass flow rate estimates in a He II phase separator. The operation safety margins of the He II heat exchanger prototype for the D2 magnet are then analyzed for the different operating conditions considered during the HL-LHC runs in case of non-nominal liquid level in the He II cold source.